Maritime-related cults in the coastal cities of Philistia during the Roman period : legacy and change - Rodan, Simona, (Archaeopress Roman archaeology ;, 2019)
This title questions the origins and the traditions of the cultic rites practised during Roman times along the southern shores of the Land of Israel. This area was known since biblical times as 'Peleshet' (Philistia), after the name of one of the Sea Peoples that had settled there at the beginning of the Iron Age. Philistia's important cities Jaffa, Ashkelon, Gaza and Rafiah were culturally and religiously integrated into the Graeco-Roman world. At the same time, each city developed its own original and unique group of myths and cults that had their roots in earlier periods. Their emergence and formation were influenced by environmental conditions as well as by ethno-social structures and political circumstances. Philistia's port cities served as crossroads for the routes connecting the main centres of culture and commerce in ancient times.